Experts’ recommendations for developing academic staff’s research skills: a case in Vietnam - Le Thanh Thao (Erudita: Journal of English Language Teaching, 2022)
Due to many reasons, research productivity from Vietnamese lecturers has not been as good as expected, and their lack of research skills is dominant. Therefore, teacher professional development in enhancing lecturers’ research productivity has received more attention from institutional administrators and policymakers. This current study was conducted to explore the types of professional development activities, according Vietnamese educational experts, are solutions to lecturers’ research productivity. Twenty experts were engaging in a conference discussing what should be done to develop tertiary lecturers’ research productivity. The meeting minutes and conference reports were used as the data for further analyses. According to the data, the experts proposed three different professional development activities for enhancing their staff’s research productivity, including organizing training events for developing lecturers’ research skills and knowledge, formulating research teams according to their interests, and encouraging them to write and publish their studies throughout rewards and punishments. The findings are expected to contribute to dealing with the current issues related to research productivity and provide researchers interested in this field with practical ideas for further research.